The group of 20: Trials of global governance in times of crisis - Ignazio Angeloni (Bruegel, 2011)
In spite of the disappointing outcome of some recent summits, notably the most recent in Cannes, the G20 is and should remain the cornerstone of the global financial architecture. Its record of performance in the last three years, reviewed in this paper, is mixed but not as unambiguously negative as critics have said. However, its effectiveness as a decision-maker has diminished over time. Enhancing the relevance and effectiveness of the G20 will require time and action on several fronts, including greater involvement and stronger commitment on the part of political leaders, better internal organisation and the development of a shared mission.
Keywords: 330; Global Governance; Internationale Zusammenarbeit; Finanzmarkt; Regulierung; Finanzkrise; G-20-Staaten